FUNDAMENTALISME GENDER DAN HETERONORMATIVITAS DALAM DUNIA POLITIK - Firnandes, Banokta; Ramlan, Ramlan; Syahrial, Syahrial; Asnizar, Andi; R, Dony.; S, Herman.; Rafli, M.; Fikri, KMS Novyar Satriawan (Yayasan Education and Social Center, 2025)
In 2016, the Italian Parliament passed a law that extended to same-sex couples most of the rights of married heterosexual couples. However, the possibility of a partner in a same-sex couple adopting the biological children of the other partner so contro-versial that it had to be deleted in order for the law to pass, thus denying lesbian and gay was parents the legal protection they need. In this article, we analyze the speeches of Parliamentarians who opposed the section of the bill concerning lesbian and gay parenthood. The empirical analysis shows different discursive strategies deployed by MPs to combat the challenges to the heteronormative family, whose common reference is the hegemonic model of gender which has characterized the resistance of the Catholic Church to the recognition of non-heterosexual reproduction and kinship. Findings highlight that the opposition to the recognition of gay and lesbian parents contributes to reiterating restrictive standards of motherhood and to maintaining the institutionalization of sexualities and reproduction within the patriarchal order. Implications of the research findings for public and social policies are discussed.